Generalized Peritonitis Secondary to Spontaneous Perforation of Pyometra in a 63-Year-Old Patient. (29th August 2013) - Abu-Zaid, Ahmed; AlOmar, Osama; Nazer, Ahmed; Azzam, Ayman; Abudan, Zainab; Al-Badawi, Ismail
Abstract : Spontaneous perforation of pyometra resulting in generalized diffuse peritonitis is extremely uncommon. Herein, we report the case of a 63-year-old woman who presented to emergency department with a 2-day history of severe diffuse abdominal pain, high-grade fever, nausea, and vomiting. Acute abdomen series was done, and upright plain chest radiograph showed free air under diaphragm. A noncontrast-enhanced computed tomography scan showed a significantly distended fluid-filled uterus measuring 10 × 7.8 × 10 cm, in addition to a single focus of perforation involving the uterine fundus and associated with presence of free air within the nondependant area. No evidence of ascites or pelvi-abdominal lymphadenopathy was identified. A preoperative diagnosis of generalized peritonitis secondary to spontaneous perforation of uterus was established. Subsequently, patient underwent urgent exploratory laparotomy which revealed pus-filled uterus with perforated fundus. Diagnosis of generalized peritonitis secondary to spontaneous perforation of pyometra was established. Consequently, patient underwent total abdominal hysterectomy with bilateral salpingo-oophorectomy, as well as thorough drainage and irrigation of pelvi-abdominal cavity. Postoperatively, patient was admitted to intensive care unit. Histopathological examination of uterus was negative for malignancy, and surgical culture grew Streptococcus constellatus . Patient had an uneventful recovery. Moreover, a brief literature review on pyometra is presented.